Impact of Geopolitical Risks on the Stock Market : Evidence from Large, Mid, and Small-Cap Stocks - Faniband, Muhammadriyaj; Jadhav, Pravin (Arthshastra Indian Journal of Economics & Research, 2023)
Purpose : This paper studied the impact of geopolitical risks (GPR) in the top 10 economies on India's large-cap, mid-cap, and small-cap stocks. Methodology : For the investigation, we employed the quantile regression technique using a monthly dataset from January 2004 to December 2020. Findings : We discovered some extremely interesting and valuable outcomes. First, geopolitical risk threats (GPRT) and China had a significant impact; additionally, GPR, geopolitical risks acts (GPRA), France, Germany, India, and the UK had a considerable impact; Canada, Japan, South Korea, and the USA had negligible impacts; and Italy had no impact on large-cap and mid-cap stocks. Second, GPRT and China had a significant impact; GPR, GPRA, India, and the United Kingdom had a considerable impact; and Canada, France, and Germany had a minimal impact on small-cap stocks. The aggregate impact of global and country-specific GPR on Indian LMS stocks was not homogeneous, showing that GPR in these economies did not uniformly influence Indian LMS stocks. Practical Implications : Our findings could assist investors in identifying market patterns, managing portfolio risk, anticipating probable stock market changes, and adjusting their investing plan accordingly. By implementing our results into their investing strategy, investors might be able to earn higher returns or minimize risk, and improve their total investment performance. Originality : As far as we know, this is the first study that looked at the impact of GPR in the top 10 economies on Indian large-cap, mid-cap, and small-cap equities.